Educação e ensino de Libras em escolas inclusivas do Ensino Médio: avanços, limitações e perspectivas - Bezerra, Tiago Codogno (2024)
This master's dissertation, carried out by a Deaf researcher - Tiago Codogno Bezerra - focuses on reflecting on the educational and social inclusion of deaf students in secondary schools in inclusive mainstream schools. The problem generating this study is characterized by the discrepancy of the inclusion of deaf students in an environment unfavorable to the interaction between deaf and hearing students, deaf students and the school community, without the offer of Libras in the High School curriculum, even though there is a series of laws related to the subject, it is observed that only Elementary and Middle School, to a certain extent, and Higher Education are contemplated with the teaching of Libras in the curriculum. Therefore, we are discussing the need to include the discipline of Libras in the curriculum of secondary education in inclusive schools in all education systems, considering the regulations of Decree 5626/2005 and other legislation related to Libras and Libras classes attended by deaf and hearing (non-deaf) people. This context is related to sociocultural premises and the anthropological conception of deafness, by outlining essential parameters for the constitution of the Being Deaf as a full subject of rights. The aim of this research is therefore justified: to analyze the conceptions about teaching Libras in the school education of deaf and hearing high school students in inclusive schools from all education networks based on reflections on the reality of the Deaf Community and the legal deliberations of educational and linguistic policies in promoting the educational and social inclusion of deaf people. The theoretical basis of the research was based on authors such as: Antonio Gil, Antonio Chizzotti, Audrei Gesser, Carlos Skliar, Cecília Moura, Gladis Perlin, Karin Strobel, Paulo Freire, Ronice Quadros, considering the contribution of their productions to a critical analysis. Using a qualitative methodological approach, bibliographical research and documental analysis were used as methodological procedures, in order to develop a critical understanding of conceptions and positions regarding the school curriculum, considering its relationship with the deaf community.We found that legislation and documents do not require the inclusion of Libras in high school, which does not favor the educational inclusion of Deaf people. We verified that the legislation and documents mention the need for sign language throughout basic education, however, the inclusion of the discipline Libras in high school does not happen in practice, which does not favor the educational and social inclusion of deaf teens and young people